THE EFFECT OF MANUAL THERAPY INTERVENTIONS ON SUBJECTIVE COMPLAINTS OF VERTIGO PATIENTS - Santoso, Totok Budi; Irfan, Naufal (Universitas Muhammadiyah Surakarta, 2021)
Centrral vertigo is a symptom caused by diseases originating from the central nervous system, both at the center of integration (cerebellum and brain stem). The dangers of central vertigo include increasing the risk of accidents while driving, causing falls due to loss of balance, disturbing hearing, interfering with daily activities, becoming a stroke or other problems in the brain. This physiotherapy treatment for the treatment of central vertigo uses manual therapy techniques, with the aim of freeing up the vertebral artery intratment. This study aims to determine whether there is an influence of manual therapeutic intervention techniques on subjective complaints of central vertigo. Observational research type, research design in this study is A-B-A design which has 3 phases. Research Samples amounted to 13 respondents. The sampling technique used was purposive sampling. central vertigo measuring instrument using Vertigo Symptsom Scale- Short Form (VSS-SF). Analysis of the data in this study is a description of the picture obtained from graph analysis and the ratting scale observation process based on measurement of behavior. Based on the results of interventions with myofascial release, traction and oscillation in 13 respondents, the average VSS-FS score before being given an intervention was 21.23 and after being given an intervention the average VSS-FS score was 2.08, so this therapy was effective in reducing entrapment neck due to vertigo with the results of the VSS-FS score decreased significantly by 19.15. The conclusion of this study is that there is an effect of manual therapy with the Myofascial release, traction and oscillation techniques which are very effective in healing central vertigo.